Comportamiento del tejido periodontal en modelo bidimensional de EF de un molar sometido a carga ortodóntica - O´’Connor Blanco, Joan; Rodríguez Madrigal, Melchor; Calás del Castillo, Héctor; Felipe Garmendia, Ángel Mario; Leija Salas, Lorenzo (Revista Mexicana de Ingenieria Biomedica, 2007)
In this work, a Finite Element bidimensional model of the Mandibular Right First Molar (MRFM) is developed, to describe the Tooth – Periodontal Ligament (PDL) – Bone system behavior, submitted to tensions and deformations induced by the loads generated using orthodontic appliances. This model has into account the complex geometry of the system and finally, we focus on a comparison of linear elastic and linear viscoelastic PDL behavior with other literature results reported.